"Mind the (Policy-Implementation) Gap": Transport decarbonisation policies and performances of leading global economies (1990–2018). (May 2021) - Tsoi, Ka Ho; Loo, Becky P.Y.; Banister, David
Highlights: Decoupling of transport carbon emissions is evaluated in 16 countries over 29 years. A nine-component strategic framework that addresses the policy-implementation gap is adopted. Good practices of transport decarbonisation were identified. Multi-instrumentality and target-setting are key factors of transport decoupling. Future policies need to bridge the policy-implementation gap by integrating local contexts. Abstract: Despite a series of transport decarbonisation initiatives, transport carbon emissions have been growing in both absolute and relative terms since 1990, and this is contributing to climate change. This study scrutinises the decoupling experiences of transport carbon emissions in 16 selected countries, including both developed and developing countries, over a 29-year timeframe (1990–2018). Resting upon the concept of socio-ecological resilience, collaborative planning and policy-implementation gap, a new conceptual framework is proposed to understand transport decarbonisation policies. In doing so, data of transport carbon emissions and Real Gross National Income in Purchasing Power Parity (based 2017) are first analysed. Progress of decoupling is then categorized for each country in every five-year period (a total of 96 data points). We then select consecutive periods when a country moves towards absolute decoupling (i.e. improvement) or deviates from it (i.e. worsening) and identify relevant policy instruments implemented based on a nine-component strategic framework that addresses the policy-implementation gap. Results indicate that defining clear sectoral objectives in action plans and integrating a holistic policy package to reinforce sustainable transport is pivotal. While there are no magic bullets to achieve transport decarbonisation, the strategic framework can help enhance policy effectiveness by formulating context-specific strategies.